Professional Teacher Competencies for Learning Quality in Vocational Education - Chotijah, Hindun Yafa; Suparman, Suparman; Kusumaningtyas, Dian Artha; Sulisworo, Dwi (Journal of Vocational Education Studies, 2025)
Learning Quality requires teachers who are competent in pedagogical, professional, social, and personality aspects. Teachers who have high competence can manage classes effectively, understand student needs, and apply innovative learning methods. Along with curriculum changes and technological developments, improving teacher competence in vocational school is urgent to create a more interactive and meaningful learning process. This study uses a qualitative method with a literature study approach to analyze strategies for improving teacher competence in vocational school. Data was obtained from various academic sources that discussed teacher training, technology utilization, self-evaluation, and the role of the teacher community. This study concludes that improving teacher competence in vocational school is a key factor in realizing effective learning. With the right strategy, it is hoped that the quality of education will increase so as to produce competitive graduates. The study recommends sustainable policies to support teachers' professional development in accordance with current educational needs.